The technology of discovery : radioisotope thermoelectric generators and thermoelectric technologies for space exploration - Woerner, David Frederich (Wiley, 2023)
"Radioisotope Thermoelectric Generators (RTGs) produce continuous, quiet electrical power for spacecraft exploring our solar system and the space beyond. These generators use thermoelectric technologies to convert heat produced by the natural decay of radioisotopes into electrical power. Two leading thermoelectric material systems have emerged as contenders to supplant currently available thermoelectric materials. Each is at a differing level of readiness for flight. Both are poised to emerge from the laboratory and be brought to production for newer, potentially more powerful RTGs. This should enable spacecraft and mission designers to save on mass and radioisotope fuel consumption. In addition, one of the technologies is so efficient and powerful as to enable new mission types."--